Aplicação de rejeitos de mineração na degradação de corante utilizado em laboratório de análises clínicas por processo Fenton - Biazati, Luciana Brunhara (2022)
Dyes, widely used in clinical analysis laboratories, are an environmental concern due to the high volume of wastewater produced. This work verified the possibility of an alternative treatment to the conventional ones to avoid the inadequate disposal of these laboratory effluents in the environment. The Fenton process is an efficient Advanced Oxidative Process for wastewater treatment. In this sense, the ferrites produced from iron mining tailings were evaluated as catalysts in the Heterogeneous Fenton reaction in the degradation of the crystal violet dye used in the Gram staining technique. A design of experimental named Central Composite Rotational Design (CCRD) was applied to identify the best conditions of ferrite mass and hydrogen peroxide concentration. The best results were with AM1 ferrite and the response surface made it possible to observe an increase in the degradation of the dye with the increased concentration of hydrogen peroxide due to the generation of more reactive species in the reaction medium. The maximum degradation was 93,00 % when using 400,00 mg.L-1 of H2O2 and 20,00 mg of ferrite. The mathematical model estimated a crystal violet degradation of 93,00 % after 60 minutes of reaction and under optimal conditions found by planning, corresponding to 373,34 mg.L-1 of hydrogen peroxide and 18,39 mg of ferrite. The catalysis results performed with ferrites AM2, AM3 and AM4 showed that the variables ferrite and hydrogen peroxide were not significant, either linearly or quadratically, in the degradation of crystal violet, despite showing a maximum degradation of 80,46 %, 70,68 % and 70,10 %, respectively. The results prove that the use of tailings as a source of ferrite in the Fenton reaction is promising, in addition to presenting the foundations of the understanding of the main phenomena that occur in this system, thus enabling future studies to evaluate the industrial application of this system.